A IMPLEMENTAÇÃO DE UNIDADE DE CONSERVAÇÃO E SUA INFLUÊNCIA NAS COMUNIDADES DE ENTORNO – CASO MONUMENTO NATURAL SÃO JOÃO, PRUDENTÓPOLIS – PR - Oliveira, Lauriana de Fatima Marcondes Diniz Rickli de (2019)
Apart from environmental preservation, the creation of a Conservation Unit may have effects on the economic and social context, directly and indirectly. According to the SNUC (Brazilian Nature Conservation Unit System), the public authorities are in charge of the creation, implementation and coordination of the unities, fostering Sustainable Development from the interaction of the several actors involved. The present study intended to investigate the creation and implementation of the Natural Monument “Salto São João”, as well as its influence on two surrounding communities. In this context, the present research of a qualitative character made use of a Case Study as the methodology, and of Bibliographical, Documentary and Field Research as the technique for data collection. This way, it was possible to point out that the absence of Public Consultation, Advisory Board and Management Plan during its creation and implementation contributed to the lack of community participation, in addition to the dissemination of information that could influence the entrepreneurship in the region. Because of that, it was noticed that sustainable development has been taking place, but in a slow way, and that only the agents that sought education for the entrepreneurship, with basis on the tourism in the CUs, have been prospecting and investing in new possibilities of income generation. By contrast, most of the population of the communities studied did not have a broad overview of Sustainable Development, influenced by the NMCU. In the data, it was noticed that due to the lack of Management Plan, Environmental Education was not prioritized, being the motivator of the visits to the scenic beauty of the place.